The Mongolia- China-Russia: Opportunities and Challenges to Develop Cross-Border Cooperation - Tsend, Baatar (Journal of International Studies, 2019)
The Mongolia-China-Russia Economic Corridor is in line with the common interests of the three countries in economic development and has been accelerated since its proposal. To strengthen trilateral cooperation is one of the key cooperation areas in “Program Planning for the Construction of Mongolia- China-Russia Economic Corridor”, it accords with the direction for “Belt and Road” initiative development. The Government of Mongolia, with the objective of improving its internal transport network and increasing trade and transit links between Mongolia and its neighboring countries, the People’s Republic of China (PRC) and the Russian Federation, has undertaken the upgrading of the Western Regional Road Corridor (WRRC). The WRRC connecting Yarant at the Mongolia/China border and Ulaanbaishint at the Mongolia/Russia border is strategically important for the socio-economic and regional development of Mongolia, as well as improving relationships with neighboring countries. Western vertical axis develops through the following steps: 1. In order to implement regional development plans, there is a need to support rural development and urbanization, to improve infrastructure conditions, to support industries and to improve the investment environment for small and medium-sized enterprises; and also there is a need to increase investment in tourism. 2. Facilitation of trade and support for cross-border trade, services and tourism. 3. A true economic corridor will be established when government policy coincides with regional development plans. Монгол, Хятад, Оросын хил орчмын хамтын ажиллагааг хөгжүүлэх боломж, сорилт Хураангуй: Энэхүү өгүүлэлд Торгоны замын эдийн засгийн бүсийн стратеги түүний зорилго, зорилт хэрэгжилтийн өнөөгийн байдал, боломж, сорилт цаашдын чиг хандлага зэргийг хураангуйлан авч үзэв. Тодруулбал, гурван улсын эдийн засгийн коридор байгуулах хөтөлбөрийн замын зурагт орсон баруун босоо тэнхлэгийн давуу тал, гурван улсын хил дамнасан бүс нутгуудын хамтын ажиллагааг өрнүүлэн хөгжүүлж хамтдаа үр шимийг нь хүртэх боломжтой дэд бүтэц, мал аж ахуй, уул уурхай, худалдаа, эдийн засаг, аялал жуулчлал чиглэлийг судалгаандаа хамруулахын зэрэгцээ Монгол, Хятадын бизнесменүүд Оросын Баруун Сибирийн хил дамнасан бүс нутагт бизнес эрхлэх боломж, тэдний эрэлт хэрэгцээ, нийлүүлэлт, хангамж зэрэг асуудлыг ч хөндөн авч үзлээ. Монгол Улсын хил орчмын бүс нутгийн хөгжлийн асуудлыг эдийн засгийн орон зайн төлөвлөлттэй нягт уялдуулан судлахыг хичээсэн болно. Түлхүүр үг: Торгоны зам, Монгол, Хятад, Орос, ӨМӨЗО, баруун бүс, Оросын баруун Сибирын бүс нутаг, эрдэс баялаг, дэд бүтэц, транзит тээвэр-логистик, аялал жуулчлал, хөдөө аж ахуйн кластер, үйлдвэр технологийн парк, хил дамнасан худалдаа, эдийн засгийн чөлөөт бүс